Nonlinearity in cap-and-trade systems: The EUA price and its fundamentals - Benjamin Johannes Lutz; Uta Pigorsch; Waldemar Rotfuß (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
In this paper we examine the nonlinear relation between the EUA price and its fundamentals, such as energy prices, macroeconomic risk factors and weather conditions. By estimating a Markov regime-switching model, we find that the relation between the EUA price and its fundamentals varies over time. In particular, we are able to identify a low and a high volatility regime, both showing a strong impact of the fundamentals on the EUA price. The most important EUA price drivers are changes on the stock market and energy prices. The gas price and a broad European equity index affect the EUA price positively in both regimes, while the coal price and the oil price have a significant, but also positive impact only during the high and the low volatility regime, respectively. The high volatility regime is predominant in phases when economic activities are on a decrease or when institutional changes harm the confidence in the stringency of the EU ETS. This holds during the recession of 2008 and 2009, as well as during 2011 and 2012 when the debt crisis impaired the European economic outlook.
urn:nbn:de:bsz:180-madoc-330020
Keywords: C22; C58; G13; Q50; 330; EU ETS; EUA Price Fundamentals; Markov Regime-Switching